Construction visuelle de la désobéissance civile : l’exemple de Tsunami Democràtic - Ludivine Thouverez (Amnis)
This paper analyzes the use of images in the communication strategy of the social movement Tsunami Democràtic in 2019. Based on the theoretical works of Michael Halliday in systemic functional linguistics and Gunther Kress and Theo van Leeuwen in visual communication, this study demonstrates that the images published on the social network Twitter have been a powerful instrument of persuasion and that the representation of the social actors involved in the souverianist conflict had two main objectives: encourage civil disobedience and draw public international opinion to the political situation in Catalonia.